The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1002/eqe.4290110507
|View full text |Cite
|
Sign up to set email alerts
|

On the application of the mode‐acceleration method to structural engineering problems

Abstract: Mode‐superposition has been extensively used in computing the dynamic response of complex structures. Two versions of mode‐superposition, namely the mode‐displacement method and the mode‐acceleration method, have been employed. The present paper summarizes the results of a systematic study comparing the accuracy of the mode‐displacement and mode‐acceleration methods when applied to structures with various levels of damping or various excitation frequencies. The paper also discusses several details concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(22 citation statements)
references
References 3 publications
0
18
0
1
Order By: Relevance
“…While, the mode acceleration method (MAM) is able to reduce errors by including the effects of the truncated modes using a static analysis [16].…”
Section: Harmonic Response Analysismentioning
confidence: 99%
“…While, the mode acceleration method (MAM) is able to reduce errors by including the effects of the truncated modes using a static analysis [16].…”
Section: Harmonic Response Analysismentioning
confidence: 99%
“…Generally, the MAM has a higher accuracy than the MDM in the case of using the same number of modes and can easily be implemented. Detailed comparisons between the computing accuracies of both methods have been made [19,20]. It concluded that the MAM outperformed the MDM in all cases.…”
Section: The Combined Methods Of Pem and Mammentioning
confidence: 95%
“…Furthermore, the accuracy and effectiveness of the dynamic response can be improved by using static correction or dynamic correction via mode acceleration, which accounts for the contribution of truncated modes, and thus reduce the laborious calculation as well [7,8]. The exemplary analysis also shows that undamped modes are not the best vector basis to reduce the structure freedom.…”
Section: Classically Damped Linear Systemmentioning
confidence: 98%